The Concept of Dzari'Ah on Preventing Transmission of Covid-19 (PSBB and PPKM Government Policy Analysis Study) - Miskari Miskari (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2022)
This study will comprehensively discuss the spread of Covid-19, which until now continues and continues to grow and even gives rise to new variants. Therefore, several countries have decided on several policies to stop the spread of the Coronavirus. Not Indonesia, one of the countries affected by COVID-19, has also issued several important guidelines. The government is the party that implements and takes action in giving PSBB and PPKM policies. The policy regulates various aspects of people's lives, ranging from tightly closed education aspects to learning from home (online), aspects of work, implementation of work from home (WFH), and aspects of worship (adjusting the distance of prayer), to closing places of worship to the public. . This research method uses a literature study that uses documentation techniques in finding data. The approach used is normative by analyzing government policies using Dzari'ah theory. The results of this study indicate that the guidelines taken by the government regarding PSBB and PPKM follow what was taught by the Prophet Muhammad. This policy was implemented and followed by the companions of the Prophet as well. This policy aims to maintain the health and strength of Muslims spiritually and physically.